If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying V = (60 + -2x)(40 + -2x)(x) Reorder the terms for easier multiplication: V = x(60 + -2x)(40 + -2x) Multiply (60 + -2x) * (40 + -2x) V = x(60(40 + -2x) + -2x * (40 + -2x)) V = x((40 * 60 + -2x * 60) + -2x * (40 + -2x)) V = x((2400 + -120x) + -2x * (40 + -2x)) V = x(2400 + -120x + (40 * -2x + -2x * -2x)) V = x(2400 + -120x + (-80x + 4x2)) Combine like terms: -120x + -80x = -200x V = x(2400 + -200x + 4x2) V = (2400 * x + -200x * x + 4x2 * x) V = (2400x + -200x2 + 4x3) Solving V = 2400x + -200x2 + 4x3 Solving for variable 'V'. Move all terms containing V to the left, all other terms to the right. Simplifying V = 2400x + -200x2 + 4x3
| 2x+4.2=6.6 | | 3y+7=4x-7y+9 | | -4(6-x)+8=4-6(x+2) | | g(-4)=-2(-4)-5 | | 6.7+x=0.5 | | 12*-2=10 | | (7x^3-5x^2+8x)+(4x^3+7x^2-10x)= | | 5x-6y=-40 | | 5x-7y+4x-2y= | | 8.1a=4.7 | | 19.50+2.50a=49.50 | | 5(5x+9)=(-x-7) | | 14y-5(3-2y)=0 | | 3x+5=7x-16 | | 6s-(25-11)=47 | | 5(5x+9)=-x-7 | | 5(x+2)+2x=0 | | 8[3+8(4-3)]= | | F(x)=(7-4x)(0.5x+3) | | 144x=8 | | F(x)=(7-4x)(0.5+3) | | 2(x+5)-20+3x= | | -8(6n+2)+3(5n-4)=-28 | | 2(x+7)10=4(x+5) | | 9x^2+64+60=0 | | 5(x+1)+3=25 | | 7x-21=4-24x | | 0.15t^2-43t+1000=0 | | 3x-7=1.1x-19 | | 38=66 | | x^2-10x+30=6 | | 3x+14y= |